Analisis Kerentanan Sosial Ekonomi Kabupaten Magelang Tahun 2016 - Mizan, Muhammad; , Drs. M. Musiyam, M.TP; , Dra. Umrotun, M.Si (2016)
This study entitled "Socio-Economic Vulnerability Analysis Magelang District 2015)", the purpose of this study to determine; (1) mapping of the spatial distribution of the level of economic vulnerability in Magelang District, (2) analyzing whether the associated factor in the vulnerability of the economy of a region in the district of Magelang. The method used in this research is quantitative with a final score calculation Hierarchy is by using AHP (Analysis Hierarchy Process) using the analysis of secondary data from BPS Magelang regency. Data collected consist of; Inflation, per capita income, population density, Population, HDI (Human Development Index). The results showed: The level of social and economic vulnerability Magelang District 2015 consists of two classes, namely low class and the class is and the factors associated to the low quality of the socio-economic Magelang regency in 2015 is IPM (health, education, spending per capita) is the score being with the level of 5x and 3x the weight is more important than the other four variables. The second is located on the Population Density many poor or very poor scores with a weight of 1 / 5x - 3x more important than the other four variables.